Effects of the Early Start Denver Model on emotional dysregulation and behavior problems in children with Autism spectrum disorder - Wan-Xia Liu; Ling Shan; Chun-Li Li; Yu-Mo Liu; Yang Xue; Yu-Ling OuYang; Fei-Yong Jia (BMC Pediatrics)
Abstract Background Most previous studies have focused on the clinical efficacy after intervention of ESDM, particularly in core symptoms. However, only a few have paid attention to the effectiveness of ESDM on emotional dysregulation and behavior problems in children with ASD. This study aimed to explore the effect of the ESDM on addressing emotional dysregulation and behavior problems in children with ASD in China, as well as its correlation with core symptoms of ASD. Methods A total of 319 children aged 1.5 to 5 years were included in this study and received treatment based on the ESDM intervention program Baseline assessment (T0) was conducted before intervention, including Children Behavior Checklist (CBCL), Autism Behavior Checklist (ABC) and Childhood Autism Rating Scale (CARS). All children with ASD were examined in the assessment (T1) after 12 weeks of treatment. Emotional dysregulation and behavior problems in children with ASD were measured using CBCL, while ABC and CARS were used to evaluate the core symptoms. Results In the T1 assessment, the core symptoms of children with ASD in ABC and CARS showed significant differences. Subscale scores of ABC and the severity of CARS, including senses, relationships, stereotypes objects to use, self-help and social also exhibited significant differences. The children showed significant differences in both total score and subscale scores of CBCL(P < 0.05), which included emotionally/reactive, anxious/depressed, somatic complaints, withdrawal, sleep problems, attention problems, aggressive behavior, internalization and externalization. The children demonstrated significant differences in scores of CBCL-AAA (P < 0.05), taking into account the combined total of attention, aggression and anxious/depressed CBCL T scores. In addition, a consistent positive correlation was observed between the overall scores of CBCL and the core symptoms of children with ASD as indicated by ABC and CARS in both T0 and T1(P < 0.01). In T0, the CBCL-AAA scores were positively associated with the core symptoms of children with ASD as reflected by CARS(P < 0.01), as well as senses of ABC( P < 0.05). During T1, a noteworthy significant positive correlation was observed between the CBCL-AAA scores and the core symptoms of children with ASD as indicated by both ABC and CARS assessment (P < 0.05). Conclusions Children with ASD benefit from ESDM, not only in terms of improving their core symptoms, but also in terms of improving their emotional dysregulation and behavior problems, and ESDM could be considered as one of the early treatment options for overall psychological promotion. The core symptoms of children with ASD are significantly associated with emotional dysregulation and behavior problems in young children, both cross-sectionally and prospectively for the short term over time. Emotional dysregulation and behavior problems represent an important comorbidity, and could be considered as potential treatment targets for treatment for improving emotional stability in ASD.